A higher order time domain panel method for linear and weakly non linear seakeeping problems. - Ruggeri, Felipe (2016)
This thesis addresses the development of a weakly non-linear Higher Order Time Domain Rankine Panel Method (TDRPM) for the linear and weakly non-linear seakeeping analysis of floating offshore structures, including wave-current interaction effects. A higher order boundary elements method is adopted based on the body geometry description using Non-uniform Rational B-splines (NURBS) formulation, which can be generated by many standard Computed Aided Design (CAD) softwares widely available, and the several computed quantities (velocity potential, free surface elevation and others) are described using a B-spline formulation of arbitrary degree. The problem is formulated considering wave-current-body interactions up to second order effects, these ones considering the terms obtained by interaction of zero/first order quantities. In order to provide numerical stability, the Initial Boundary Value Problem (IBVP) is formulated in terms of the velocity potential and the local acceleration potential, the later used to predict the hydrodynamic pressure accurately. The zeroth order problem is solved using the double-body linearization instead of the Neumman-Kelvin one in order to allow bluff bodies simulation, leading to very complex expressions regarding the m-terms computation. The method adopts the Rankine sources as Green\'s function, which are integrated using Gauss quadrature in the entire domain, but for the self-influence terms that are integrated using a desingularized procedure. The numerical method is verified initially considering simplified geometries (sphere and circular cylinder) for both, first and second-order computations, with and without current effects. The derivatives of the velocity potential are verified by comparing the numerical m-terms to the analytical solutions for a hemisphere under uniform flow. The mean and double frequency drift forces are computed for fixed and floating structures and the quantities involved in these computations (wave runup, velocity field) are also compared to literature results, including the free floating response of a sphere under current effects. Two practical cases are also studied, namely the wave-induced second order responses of a semi-submersible platform and the wavedrift-damping effect evaluated through the equilibrium angle of a turret moored FPSO. For the former, some specific model tests were designed and conducted in a wave-basin.